Case Report: Can Ruptured Aneurysms in the Hypoplastic and Plexiform Posterior Inferior Cerebellar Arteries Be Safely Occluded? - Hou, Kun; Yu, Jinlu (Frontiers in Neurology, 2022)
Aneurysms arising from the posterior inferior cerebellar artery (PICA) are not rare and may originate from the proximal or peripheral segment of the PICA. However, when the affected PICA is hypoplastic and plexiform, it is difficult to occlude the aneurysm without sacrificing the parent vessel, PICA. This type of aneurysm is rare, and whether it is safe to occlude the aneurysm and the parent artery in cases of a ruptured aneurysm of the hypoplastic and plexiform PICA has not been adequately studied and is still open to debate. In this report, 2 patients with ruptured aneurysms in the hypoplastic and plexiform PICA were presented. Both patients were admitted to our hospital for subarachnoid hemorrhage. After team discussions between the neurosurgeons and neurointerventionalists, the aneurysm and parent PICA had to be occluded via endovascular treatment under general anesthesia. One of the patients developed postprocedural brainstem infarction and exhibited favorable recovery. The other patient died of pulmonary infection, although improvement in the postoperative state was observed. Although rare, aneurysms can originate from the hypoplastic and plexiform PICA. Occluding the aneurysm and hypoplastic parent PICA via endovascular treatment might be a reasonable option.